(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted at Shambat Research Station,Khartoum North for two growing seasons (2003/4 and 2004/5) toinvestigate the effects of three sowing dates (15 Dec., 15 Jan. and 15 Feb.)and five seed rates (90, 100, 110, 120 and 130 kg ha -1 ) on the yield andquality of the sets of red onion cultivar “Saggai Improved” .The firstseason gave the best vegetative growth, high total number and weight ofsets ha -1 as well as improved set quality. High levels of seed ratesincreased the total number of sets ha -1 in the first season, while they hadno effect on growth attributes and size grades per m-2 . However averageset weight decreased when high levels of seed rates were used. Earlyplanting date (15 Dec.) resulted in better plant growth as reflected inincreased leaf number plant-1 , fresh and dry weight of sets and total freshand dry weight. Significant increases in the total number and weight ofsets ha -1 , improved set quality and set weight due to early planting werealso realized